Extra Gastrointestinal Stromal Tumor Pada Ovarium, Kasus Jarang - Liana, Nana; Nizar, RZ; Asri, Aswiyanti; Novianti, Hera; Friadi, Andi (Fakultas Kedokteran Universitas Andalas, 2020)
Objective : This article objective is to describe a woman with extra gastrointestinal stromal tumor (extra GIST) in ovary; Method : A case report and literature review; The author reports a woman 54 years old with complaints of swelling in the abdomen. Tumors suspected originate from ovary with an extension to abdominal wall. The patient had history of previous ovarian tumor surgery with pathological anatomy diagnosis was thecoma. Working diagnosis of the patient was residif ovarian malignancy and then suboptimal debulking was performed. Microscopically, ovarian tumors appear cellular and diffuse, partially arranged fascicles. Cells with rounded-spindle nuclei, mitosis â‰¥ 4 per 10 HPF. The conclusion was malignant thecoma which metastasizes to peritoneum and omentum. Differential diagnosis were GIST and leiomyosarcoma. Immunohistochemistry examination was performed with Â Calretinin and CD117 to rule out the differential diagnosis. Calretinin were negativeÂ and CD117 were strongly positively smeared. Based on the morphology and positive CD117 results, diagnosis was extra GIST of ovary.; Conclusion: Extra GIST in the ovary is an unusual location so that it can be misdiagnosed as a gynecological disorder. The differential diagnosis at this location is quite limited including thecoma, fibrothecoma and leiomyosarcoma.Keywords: extra gastrointestinal stromal tumor, ovary, thecoma